A influência da ortografia na percepção e produção do inglês como língua estrangeira - Oliveira, Caio Frederico Lima Correia Novais de [UNESP] (2015)
To Brazilian learners of English as a foreign language, the acquisition of a new phonological system can be complicated by the influence of the phonological system of their native language, as well as other factors. One of these other factors is the difference between the orthographies of both languages, which, despite sharing the same writing system, have different correspondences between graphemes and phonemes. It is known that different grapheme-phoneme correspondences in English often affect the learner's pronunciation, generating deviations. Few studies have focused on the influence of the orthography of a foreign language on a learner's auditory perception. This research aimed to show that this influence occurs in auditory perception and speech production of the grapheme <s> and <ss> in intervocalic position of English words by Brazilian learners. To prove our hypothesis, we conducted four auditory perception and speech production experiments with 74 informants, generating written data and audio recordings. Our data showed that this influence exists, causing deviations in the auditory perception and in the oral production of informants. The influence of orthography is more common in cognate English words (such as basic/básico), or in words that already belong to the lexicon of Brazilian Portuguese (such as NASA). In addition, we found that the presentation of auditory input is integral to the correction of most oral deviations caused by the influence of spelling, but we also found that the latter is often required for lexical recognition. Our results point to the importance of having complementarity between the written and oral modalities, as well as the knowledge of grapheme-phoneme correspondences in Portuguese and English as a vital learning tool